2003
DOI: 10.1002/pros.10218
|View full text |Cite
|
Sign up to set email alerts
|

Negative bacterial polymerase chain reaction (PCR) findings in prostate tissue from patients with symptoms of chronic pelvic pain syndrome (CPPS) and localized prostate cancer

Abstract: A bacterial etiology for CPPS symptoms could not be demonstrated in patients with prostate cancer. The results also suggest that the prostate is unlikely to harbor bacterial normal flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Referred visceral hyperalgesia was measured as responses to mechanical stimulation of the pelvic region using von Frey filaments of five calibrated forces. Data are reported as the mean percentages of positive responses Ϯ SEMs at 14,16,18,20,22,24,26, and 28 weeks of age. (A) Responses to pelvic stimulation from 14 to 28 weeks of age (n ϭ 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referred visceral hyperalgesia was measured as responses to mechanical stimulation of the pelvic region using von Frey filaments of five calibrated forces. Data are reported as the mean percentages of positive responses Ϯ SEMs at 14,16,18,20,22,24,26, and 28 weeks of age. (A) Responses to pelvic stimulation from 14 to 28 weeks of age (n ϭ 10).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the predominantly nonbacterial nature of CP/CPPS, up to 8% of patients with CP/CPPS harbor uropathogens that have traditionally been deemed to be of no significance (25). Numerous studies have also identified bacterial DNA in prostate samples from CP/ CPPS patients (9,19,20,22,25). CP/CPPS accompanied by uropathogens is differentiated from chronic bacterial prostatitis by the requirement for clinical symptoms of pelvic pain and the lack of recurrent urinary tract infections (UTIs).…”
mentioning
confidence: 99%
“…No definitive targetable pathogen or pattern of microbial dysbiosis within prostate tissue has been identified that was clearly correlated with CP/CPPS in the absence of other confounding variables such as prostate cancer or other proper controls (82)(83)(84). A recent study by Nickel et al compared urethral and bladder urine specimens from CP/CPPS patients in the Multi-Disciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Network Study, and found differences in the CP/CPPS urinary microbiome as compared to control patients, more specifically an increase in Burkholderia cenocepacia in urethral specimens.…”
Section: The Microbiome In Urologic Chronic Pain Syndromesmentioning
confidence: 99%
“…The 16S rDNA-based techniques have been proven to be more substantially sensitive and accurate than traditional techniques that depend on microbial culture (11,12). Several studies have evaluated the presence of multiple and diverse bacterial 16S rDNA sequences in prostate biopsy tissue from BPH and PC patients (15,(24)(25)(26). In the present study, we used PCR-DGGE with 16S rDNA finger printing analysis to investigate bacterial composition in the biopsy of PC patients in the PSA grey-zone with or without hypertension.…”
Section: Discussionmentioning
confidence: 99%